Faktor-Faktor Yang Mempengaruhi Pasangan Remaja Usia 13 – 22 Tahun Untuk Melakukan Sex Bebas Di Kawasan Tretes Kecamatan Prigen Kabupaten Pasuruan - Iis Fatimawati; M. Rijal Febrianto (Akademi Keperawatan Dharma Husada Kediri, 2014)
Adolescence is a period of transition from child to adulthood. Many problems experienced by adolescents in this biological transition, for example is free sex. The purpose of this study was to determine the factors that influence teenage couples aged 13-22 years for free sex in the districts Tretes Prigen Pasuruan regency. This study used a cross sectional analytic design. Independent variable in this study is the family factor, sex education, and environment. Dependent Variabel is free sex. The sample was mostly couples teenager in Tretes Pasuruan District Prigen that totaling 34 people. Sampling technique that is accidental sampling. This study was conducted in June 2014. Results showed the majority of family factors (55.9%) is less. Factors sex education the majority (67.6%) is less. Environmental factors most (61.8.%) Is less. Teen couple who are free sex is majority (64.7%). Analysis using chi square test showed association of family factors, environmental factors, and the factor of sex education to teen couple sex free.Need for Sex explanation that correct and proper manner that is based on religious values, culture and ethics, so the teenager will avoid that are negative things and reprehensible associated with problem-free sex.